Návrhy na snížení nezaměstnanosti v okrese Prostějov - Vinkler, Luboš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Tato diplomová práce analyzuje problematiku nezaměstnanosti v okrese Prostějov od roku 2003 do konce první poloviny roku 2007. Obsahuje rozbor struktury nezaměstnaných ve vztahu k délce nezaměstnanosti, věku a vzdělání. Dále se práce zabývá analýzou problémových skupin a aktivní politikou zaměstnanosti. Součástí jsou též návrhy vhodných opatření, které by měli vést ke snížení nezaměstnanosti v regionu.

This diploma work analyzes the problems of unemployment in the district of Prostějov from 2003 till the end of the first half of 2007. It contains the structure analysis of unemployed people in relation to the lenght of unemployment, age and education. Next, the work drala with profiling of the problem groups and active policy of employment. There are suggestions of suitable measures, which should lead to reduction of the unemployment rate in the region.
Suggestion for reduction of unemployement in the district of Prostějov
Keywords: Nezaměstnanost; zaměstnanost; volná pracovní místa; trh práce; Unemployment; employment; free working places; marketplace working